DEVELOPMENT OF MATHEMATICS LEARNING MEDIA BECA GAME MATERIAL FRACTURES - Ririn Febriyanti; Ayu Triska Arianti (Jurnal Prinsip Pendidikan Matematika, 2023)
The learning process cannot be separated from learning media. One of the functions and benefits of learning media is to convey information on subject matter, evaluation questions, increase student motivation, and present material in an interesting form. Current learning media can be in the form of applications whose use is based on an Android smartphone. The purpose of this research is to produce and test the feasibility of BeCa game-based mathematics learning media for elementary students. This research is included in research and development or Research and Development (R&D). The research design refers to the Thiagarajan research model which has 4 steps (4D), namely define, design, development, and dissemination. The instrument used was a questionnaire for material experts, media experts, and students. According to the results of the development of learning media, it has five components, namely the home page, the concept map page for fraction material, the material list page for fractions, the KD & indicators page, the evaluation play list page (game). There are 2 stages of learning media trials in this research, namely small group trials and large group trials. The results of the small group trials obtained an average value for each aspect in the range of 3.4<X≤4.2 with a good category. While the results of the large group trial obtained an average value for each aspect of 3.4<X≤4.2 in the good category. The conclusion from the study is that the Beca Game learning media can be used.